Rio Grande e seus espaços de memória: a construção do Guia de Acervos da Cidade do Rio Grande - Bertotti, Valéria Raquel (2013)
This paper presents the development of the Guide of Collections of Rio Grande. Composed of bibliographic, iconographic, textual, cartographic and museological documents, such collections represent a part of the history of the city. Inserted in the Documentary Heritage Line Research, the research was conducted in five stages: preparation of data collection instrument (standard application form), identification of custodial institutions and their collections, a test to standard application form, description and, finally, elaboration of the Guide. The standard application form was created from the analysis of the International Regulation for Description of Institutions with Archival Collections and other elements of the archival field, as well as specific factors from librarianship, museology and history. The identification was performed by mapping Institutions such as Museums, Libraries, Archives, Centers of Memory and Memorials established in Rio Grande which have already had references of researchers, information about their collections in several publications and websites, with public access for visitation and / or research, although with restrictions. At the stage of description of the Institutions and their respective collections by the means of standard application form - firstly information was collected from websites and other materials related. In order to complement the information gathered, visits and interviews were conducted with employees of the respective institutions. Lastly, there have been developed a Guide to Collections with the production of indices which intend to represent the information of the collections divided in four groups: Collection Typology, prevalent themes, documentary genres and study periods. The research presents as results the development of the data collection instrument - standard application form to describe different collections which will contribute to the propagation of such collections and may serve as a basis for building other Guides. The Guide to Collections, product of this work, brings together into one instrument the description of documentary arrangement, providing distribution and correlation of disparate sources in different institutions. In this sense, the purpose of analyzing ISDIAH ( Norma Internacional para Describir Instituciones que Custodian Fondos de Archivo , freely translated as International Standard for Describing File Custodian Funds Institutions) and elements in the fields of archivology, librarianship and museology, in order to describe custodial institutions and their collections, identify and describe such collections, highlight related sources, publish the documentary collections of the city, was achieved. Also, it is important to emphasize the need to expand this research through a mapping of the heritage of the city of Rio Grande, increasing the number of institutions listed in the Guide, the creation of a database based on the data collection instrument and the development of a thesaurus to the city of Rio Grande.